Gestión de riesgos mayores para la Facultad de Ciencias de la Salud de la Universidad Nacional de Chimborazo. - Escobar Cordero, Katherine Dayan (2024)
The purpose of risk management is to identify, assess, and control any potential risks, both natural and man-made, that could affect various facilities. In this context, the objective of the research was to develop an emergency plan for the Faculty of Health Sciences at National University of Chimborazo (UNACH), in compliance with current legal regulations and with the purpose of improving accident prevention and mitigation measures. To identify the risks, an on-site inspection was carried out in the different spaces of the building, evaluating the available resources using the FEMA, MESERI matrices and the vulnerability matrix for institutions. The population studied included 2,085 users, which corresponds to the maximum capacity of the Faculty of Health Sciences. The results revealed that the main threats to the faculty are earthquakes, floods, epidemics, pests, fires, explosions, gas leaks, poisoning, assaults and civil disorder. The FEMA 154 analysis indicated a medium vulnerability, which implies that it is not necessary to reinforce the structure of the building. According to the fire assessment using the MESERI method, a medium risk was obtained with a value of 5.06. On the other hand, the vulnerability analysis for institutions showed risk levels ranging from low to medium for natural, technological and human factors. With these results, an emergency plan was designed that constitutes an effective tool to improve the response capacity to emergencies, protecting people, property and the environment.